Border cities: Out of the shadow. Issue 2 (23rd January 2022) - Sohn, Christophe; Licheron, Julien; Meijers, Evert
Abstract: Being in the sphere of influence of other cities can have benefits as it allows cities to "borrow size, " but this can also lead to competition effects known as "agglomeration shadows." This paper examines how these patterns of borrowing and shadowing differ from domestic settings when there is a national border between the cities. We find that borders moderate the normal regularities of a settlement system. Particularly, there is no shadow effect cast by larger cities across borders; borders protect. Cross‐border market integration benefits especially similar‐sized border cities. Given these unique advantages, it is time for border cities to step out of the shadows. Resumen: Estar en la esfera de influencia de otras ciudades puede tener ventajas, ya que permite a las ciudades "tomar prestado el tamaño", pero esto también puede provocar efectos de competencia conocidos como "sombras de aglomeración". Este artículo examina cómo estos patrones de préstamo y sombras difieren de los entornos domésticos cuando existe una frontera nacional entre las ciudades. Se encontró que las fronteras moderan las regularidades normales de un sistema de asentamiento. En particular, no existe el efecto de sombra que proyectan las ciudades más grandes a través de las fronteras, y de hecho las fronteras protegen. La integración del mercado transfronterizo beneficia especialmente a las ciudades fronterizas de tamaño similar. Dadas estas ventajas únicas, es hora de que las ciudades fronterizas salgan de las sombras. 抄録: 他の都市の影響下にあることは、都市が「規模を借用する(to borrow size)」ことで利益がえられる一方で、「集積の陰(agglomeration shadows)」といわれる競争効果がもたらされる可能性がある。本稿では、こうした、規模を借用すること(borrowing)と集積の陰にあること(shadowing)のパターンが、都市間に国境がある場合では、国内でのパターンとどのように異なるかを検討する。国境は決済システムの正常な規則性を緩和することが分かった。特に、大都市による集積の陰の国境を越える影響は認められないばかりか、国境による保護が認められる。国境を越えた市場統合は、特に規模の同じ国境都市に利益をもたらす。こうしたユニークな利点から、今こそ国境都市は集積の陰から抜け出すべきと考えられる。